2016
DOI: 10.4209/aaqr.2016.07.0329
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Characteristic Analysis of Particulate Matter from Diesel Engine Run on Diesel/Polyoxymethylene Dimethyl Ethers Blends Based on Nanostructure and Thermogravimetry

Abstract: This paper focuses on the nanostructural and pyrolysis characteristics of particulate matter (PM) emitted from a diesel engine fueled by three diesel/polyoxymethylene dimethyl ethers (PODE n ) blends. PM was collected using a metal filter from the exhaust manifold. The collected PM samples were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and thermogravimetric analysis (TGA). SEM and TEM analysis showed that PM generated by the 20%-PODE n blend was looser and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The nano particle emission concentration and their total area were also reported to be reduced by oxygenated fuel additives (Saxena and Maurya, 2016). Yang et al (2016) further indicated that the use of oxygenated diesel blends could affect the nanostructure and pyrolysis of PM, which was easier to oxidize and advantageous for diesel particulate filter regeneration. Additionally, as biodiesel has a higher cetane index than fossil diesel, it shortens the ignition delay, leading to an earlier start of combustion reaction (Musculus, 2002;Lin and Lin, 2011).…”
Section: Pm Emissionsmentioning
confidence: 99%
“…The nano particle emission concentration and their total area were also reported to be reduced by oxygenated fuel additives (Saxena and Maurya, 2016). Yang et al (2016) further indicated that the use of oxygenated diesel blends could affect the nanostructure and pyrolysis of PM, which was easier to oxidize and advantageous for diesel particulate filter regeneration. Additionally, as biodiesel has a higher cetane index than fossil diesel, it shortens the ignition delay, leading to an earlier start of combustion reaction (Musculus, 2002;Lin and Lin, 2011).…”
Section: Pm Emissionsmentioning
confidence: 99%
“…10 Several studies investigated different blends of OME with diesel fuel to conform to the EN590 standard, which showed a signicant reduction in local emissions for both heavy duty and passenger cars. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Under certain conditions, even a mixture of 10 vol% OME with diesel can lead to a signicant reduction in NO x and soot emissions. 12 A stoichiometric evaluation showed that already 10 vol% OME blend with diesel will correspond to ca.…”
Section: Introductionmentioning
confidence: 99%